Morphological characteristics, nutritive quality, and methane production of tropical grasses in Brazil - Lima, Danilo Montalvão; Abdalla Filho, Adibe Luiz; Lima, Paulo de Mello Tavares; Sakita, Gabriel Zanuto; Silva, Tairon Pannunzio Dias; McManus, Concepta; Abdalla, Adibe Luiz; Louvandini, Helder (Pesquisa Agropecuaria Brasileira, 2018)
The objective of this work was to evaluate three tropical forage species for their in vitro methane (CH4) production and organic matter degradability, in order to determine the relationships between forage grass nutritive quality and CH4 production. Guinea grass (Megathyrsus maximus), palisade grass (Urochloa brizantha), and signal grass (Urochloa decumbens) were evaluated. Palisade grass showed the highest organic matter, neutral detergent fiber, acid detergent fiber, lignin, and lower-crude protein content. Signal grass had the highest values for hemicellulose and neutral detergent fiber-nitrogen, and the lowest-cellulose content. Guinea grass and signal grass showed a higher-total gas production than palisade grass. Besides, Guinea grass showed an increased CH4 production, and palisade grass showed lower value for truly degraded organic matter, and reduced partitioning factor, in comparison to signal grass. An increased CH4 production was observed in cases of lower hemicellulose and paratitioning factor. The nutritive value and CH4 production of forages may be employed as parameters, aiming at the sustainability of ruminant production.